Memaknai Penderitaan Secara Kristiani - Hidayat, Elvin Atmaja (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
Suffering is a reality that everyone endures as an integral part of his/her life. As the part of human life, suffering is inevitable. For some people, suffering shakes their faith in the Benevolent God. They asked, “Why does not God eliminate the suffering if He is benevolent and omnipotent?” This paper is going to persuade the Christians to make sense of their suffering by examining the views of Scripture and the documents of the Church (especially Salvifici Doloris). Both sources show that there are a lot of meanings behind the suffering. From such explanations, we would say that suffering also serves for good. The writer invites the faithfuls to be “in peace” with their suffering. People are led to interpret suffering as a precious and valuable gift. In so-doing, people would be able to remain faithful, even become more steadfast in the midst of their suffering. The concept of God as “Father” would also helps people to be more enduring in Christian faith.